Analisis Struktur Ekonomi dan Identifikasi Sektor Unggulan Kabupaten Tuban - Krisna Dwi Andayani; Sri Muljaningsih; Kiki Asmara (Al-Buhuts, 2021)
This Research aims to find out the sector changes that drive economic growth in East Java, changes in the same sector in East Java, relatively faster sector changes than other sectors in Tuban district, changes in the base sector in Tuban district, and changes in the type of areas in Tuban district. With Location Quotient Analysis method, Shift Share, and Klassen Typology. The results of the analysis of shift share PR 2015-2019 showed there are changes in sectors that drive economic growth in East Java, the results of the analysis of PS 2015 -2019 also showed changes in the same sector in East Java, the results of DS analysis showed a relatively faster change in the sector than other sectors in Tuban district. The results of the Location Quotient analysis show that there was a change in the base sector in Tuban Regency from 2015 to 2019 from 5 sectors to 6 base sectors with an enhancer sector namely the information and communication sector. Changes did not occur in the type of district tuban from 2015 - 2019 remains included in the quadrant to IV